PENTINGNYA PENDIDIKAN KARAKTER GUNA MENINGKATKAN MORALITAS PESERTA DIDIK DI MAS NURUL FADHILAH - Rifda Ramadina; Abdul Fattah Nasution; Khoirunnisa Fadilla Rambe; Hafiz Yusuf Nasution (Cemara Education and Science, 2024)
ABSTRACT The aim of this research is to determine the most important aspects of character education in order to improve student morale at MAS Nurul Fadhilah. This research is motivated by the moral crisis occurring among students today, which is exacerbated by the current situation and can have a significant impact on the development of character and morality among students. Looking at world developments, currently many students use technology for entertainment and have poor morals and social skills in society. Therefore, character education is very important to develop a high-quality generation and foster a sense of responsibility. Character education consists of God Almighty, obeying legal rules, implementing interactions between communities, implementing spiritual, moral and ethical values in Indonesian society. This research uses qualitative methodology. The data collection techniques used were library and field studies. Literature review was carried out by looking for credible journals. Next, case studies are carried out through interviews and observations. The informants in the research were one of the teaching staff and two students at MAS Nurul Fadhilah